Asymmetrical Information Between Smes And Banking: A Perspective From Signaling Theory - Virginia, Winda Ayu; Misran (Agregat: Jurnal Ekonomi dan Bisnis, 2025)
The aim of this research will be to look more deeply into the problems faced by MSMEs in obtaining capital from banks due to the existing information asymmetry. This study uses a qualitative method that aims to explore the conditions in the field. The data analysis model used in this study is descriptive, qualitative, and quantitative, presented in the form of tables and images with descriptive statistics so that a comprehensive picture is obtained that can explain the research questions. Data collection techniques use questionnaires in the form of closed and open questions, interviews, and documentation.We find that there are information asymmetry between customers and banks. The information signal given by customers cannot be understood properly by bank officers because the information conveyed is in accordance with the SOP set by the bank. Customers modify the information given to bank officers so that the credit given is approved for several reasons such as insufficient collateral, other urgent needs, paying off debts from other creditors (take over), for new businesses, education costs and helping families. The bank's developed instrument should have identified the customer's signal. The bank can ignore this signal because the customer has a credit score that is not problematic and pays installments on time.